Al-Qur’an dalam Paradigma Antropologi: Telaah Relasi Teks dan Konteks dalam Dinamika Budaya - Muhammad Adlan Nawawi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This paper discusses the interpretation of the Qur'an within socio-cultural phenomena that can be studied anthropologically. By using an anthropological perspective, researchers can understand the practices and variations in human religious interpretation across space, time, and space. An anthropological approach can be used to understand the relationship between religion and various issues in human life, thus demonstrating the correlation of religion with various phenomena in human life. In reading holy texts such as the Qur'an, anthropology seeks to establish the relationship between the textual content and the various cultures that exist in society. With an anthropological perspective, the study of the Qur'an encompasses not only its understanding as a holy book with its various interpretations, but also the context of these interpretations in the real life of everyday people.